Long non‐coding RNA TTN‐AS1 facilitates tumorigenesis of papillary thyroid cancer through modulating the miR‐153‐3p/ZNRF2 axis. (25th March 2019) - Cui, Zhenghui; Luo, Zhiyan; Lin, Zimei; Shi, Liuhong; Hong, Yurong; Yan, Caoxin
Abstract: Background: Long non‐coding RNAs (lncRNAs) are crucial modulators in the tumorigenesis of numerous cancers, including papillary thyroid cancer (PTC). However, it is unclear whether lncRNA TTN antisense RNA 1 (TTN‐AS1) can regulate PTC progression. The present study aimed to reveal the mechanism and function of TTN‐AS1 in PTC. Methods: TTN‐AS1 expression in 92 pairs PTC tissues and four PTC cells was measured via a quantitative reverse transcriptase‐polymerase chain reaction assay. The relationship of TTN‐AS1 expression and clinical pathological features of PTC patients was analyzed using a chi‐squared test. The biofunction of TTN‐AS1 in PTC was identified by loss or gain‐of‐function assays. Based on bioinformatics analysis and mechanism experiments, the molecular mechanism of TTN‐AS1 was analyzed and identified. Results: A high level of TTN‐AS1 was observed in PTC tissues and cells. The expression level of TTN‐AS1 is possibly associated with lymphatic metastasis, TNM stage and the overall survival of PTC patients. Functionally, TTN‐AS1 knockdown inhibited cell proliferation, migration, invasion and epithelial–mesenchymal transition in PTC, whereas overexpression of TTN‐AS1 led to the opposite results. Mechanistically, TTN‐AS1 acted as a competing endogenous RNA by sponging microRNA‐153‐3p (miR‐153‐3p) to elevate zinc and ring finger 2 (ZNRF2) expression. Additionally, a high level of TTN‐AS1 in PTC was closely correlated with the activity of the phosphoinositide 3‐kinase (PI3K)/Akt/mechanistic target of rapamycin (mTOR) pathway. Conclusions: The findings obtained in the present study indicate that TTN‐AS1 facilitated PTC progression by regulating the miR‐153‐3p/ZNRF2 axis and activating the PI3K/Akt/mTOR pathway.